Enhancing Diabetes Self-Monitoring via Mobile App: An MVVM and Firebase Approach - Azimi, Indra; Akmal, Muhammad Reihan (Jurnal Informatika Ekonomi Bisnis, 2026)
Diabetes Mellitus is a chronic metabolic disorder that demands continuous and disciplined self-management to prevent severe systemic complications. Despite its critical importance, patient adherence to regular blood glucose tracking, dietary restrictions, and medication schedules remains low in Indonesia. This study addresses these challenges by developing and evaluating DiabetesKu, a native mobile health application designed to facilitate independent diabetes management. Engineered using Android Studio with the Kotlin programming language, the system implements the Model-View-ViewModel MVVM architecture to decouple business logic from the user interface, while leveraging the Firebase cloud ecosystem for secure, real-time data synchronization and automated reminder deployment. The application integrates core features such as interactive health logging, contextual diabetes education, medication alarms, macronutrient tracking, and direct consultation channels. To evaluate its structural integrity and operational viability, a multi-tiered testing framework was applied. Automated Black Box testing using the Espresso framework across ten critical functional scenarios achieved a 100% success rate, confirming high code stability. Furthermore, field usability evaluations involving active diabetes patients demonstrated an outstanding cumulative satisfaction rate of 91.7%, with users highly praising its clinical usefulness, navigational simplicity, and visual accessibility. The empirical results demonstrate that DiabetesKu is a highly reliable and user-accepted digital health solution capable of promoting patient compliance and reinforcing independent lifestyle control in daily diabetes care.